The Role of the Constitutional Court in Maintaining Democracy and Strengthening the Rule of Law: Critical Evaluation - Edyson, David; Alfariza M, Raden Mahaputra; Hasibuan, Armando Benyamin (CV. Rayyan Dwi Bharata, 2024)
The Constitutional Court (MK) plays a crucial role in safeguarding democracy and upholding the rule of law in Indonesia. MK holds extensive authority to conduct judicial review, settle election disputes, resolve conflicts between state institutions, and adjudicate petitions concerning citizens' constitutional rights. MK's performance has garnered mixed evaluations. Appreciation is given for its role in strengthening the constitution, enhancing democratic quality, and fostering public trust. However, criticisms have also emerged regarding inconsistencies in rulings, lack of transparency, and a high volume of cases. The independence and accountability of MK are paramount to ensuring its objectivity and impartiality in fulfilling its functions. Factors influencing MK's independence include the selection process for judges, their term of office, and their immunity from prosecution. Mechanisms for MK's accountability involve annual reporting, civil society oversight, and media coverage. MK faces both prospects and challenges in the future. It is anticipated that MK's role in upholding democracy and the rule of law will continue to grow, and public trust in MK will be maintained. The challenges MK confronts include the complexity of legal issues, potential political intervention, and safeguarding public confidence.